Polyacrylonitrile/Crown Ether Composite Nanofibres With High Efficiency for Adsorbing Li(I): Experiments and Theoretical Calculations - Ding, Tao; Wu, Qian; Zheng, Mianping; Nie, Zhen; Li, Min; Peng, Suping; Wang, Yunsheng; Yu, Xudong; Qian, Cheng; Tang, Si; Wang, Mingliang (Frontiers in Energy Research, 2021)
Lithium, as the lightest alkali metal, is widely used in military and new energy applications. With the rapid growth in demand for lithium resources, it has become necessary to improve the effectiveness of extraction thereof. By using chemical grafting and electrospinning techniques, nanofibres containing crown ether were developed for adsorbing Li(I) from the brine in salt lakes, so as to selectively adsorb Li(I) on the premise of retaining specific vacancies of epoxy groups in crown ether. In lithium-containing solution, the adsorbing materials can reach adsorption equilibrium within three hours, and the maximum adsorption capacity is 4.8 mg g−1. The adsorption mechanisms of the adsorbing materials for Li(I) were revealed by combining Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), and X-ray photoelectron spectroscopy (XPS) with density functional theory (DFT) calculation. The results indicated that in crown ether, O in epoxy groups was coordinated with Li(I) to form Li–O and four O atoms in the epoxy groups were used as electron donors. After coordination, two O atoms protruded from the plane and formed a tetrahedral structure with Li(I), realising the specific capture of Li(I). By desorbing fibres that adsorbed Li(I) with 0.5-M HCl, the adsorption capacity only decreased by 10.4% after five cycles, proving ability to regenerate such materials. The nanofibres containing crown ether synthesised by chemical grafting and electrospinning have the potential to be used in extracting lithium resources from the brine in salt lakes.